Pediatric head and neck malignancies in sub-Saharan Africa (2012)
Introduction: Cancers are relatively rare in children however recent reports suggest that malignancies are becoming a major source of pediatric deaths. Method: Using the database of the cancer registry of the University College Hospital, Ibadan we reviewed all newly diagnosed cases of head and neck cancers in children under 19years old at the hospital between 1981 and 2008. Results: A total of 1,021 cases of Head and Neck cancers were seen in children. The hospital based incidence of pediatric head and neck cancers is 36 cases per year. There were 627 males and 394 females [M:F ratio of 1.6:1] with mean ages of 8.21 and 7.70 years respectively. Boys were more affected than girls in all years of life while the peak age of onset for both sexes is the third year of life. The commonest anatomical site involved is the eye/orbit; other common sites were the nasopharynx, paranasal sinuses, nasal cavity and thyroid gland. Neural malignancies constitute the commonest malignancies seen (35.3%), other are lymphomas (33.1%), squamous cell carcinoma (9.1%) and soft tissue sarcoma (8.6%). Retinoblastoma is the commonest lesion seen among the patients with a slight male preponderance [M:F ratio of 1.2:1] Burkitt lymphoma (BL) is seen in all age groups but there is greater frequency in the older ages. The incidence of carcinomas is higher in the older age groups, relatively rare lesions like Hodgkins lymphoma and thyroid malignancies are almost exclusive to older children. Conclusion: The pattern of head and neck malignancies in children in sub-Saharan Africa is changing; dominant lesions like lymphomas are being gradually replaced by other malignancies such as neural malignancies, soft tissue sarcomas and squamous cell carcinoma